Secrecy Rate Maximization for Reconfigurable Intelligent Surface Aided Millimeter Wave System With Low-Resolution DACs - Xiu, Yue; Zhao, Jun; Sun, Wei; Zhang, Zhongpei (IEEE communications letters, 2021)
In this letter, we investigate the secrecy rate of a reconfigurable intelligent surface (RIS)-aided millimeter-wave (mmWave) system with low-resolution digital-to-analog converters (LDACs). Compared to the RIS-aided systems in most existing works, we consider how to alleviate the hardware loss and improve the secrecy rate by using RIS. In particular, we formulate a secrecy rate maximization problem with hardware constraints. To handle the problem, an alternating optimization (AO)-based algorithm is proposed. Specifically, we first use the successive convex approximation (SCA) method to obtain the transmit beamforming. Then, the element-wise block coordinate descent (BCD) method is used to obtain the RIS phase shifts. Numerical results demonstrate that the RIS can mitigate the hardware loss, and the proposed AO-based algorithm with low complexity outperformances the baselines.